2017
DOI: 10.1002/pop4.181
|View full text |Cite
|
Sign up to set email alerts
|

The Relational Experience of Poverty: Challenges for Family Planning and Autonomy in Rural Areas

Abstract: This is a qualitative study of a family planning education program in New York State using in‐depth interviews with 16 low‐income participants. The study demonstrates how challenges faced by the rural poor in family planning and health autonomy are exacerbated by lack of social support and isolation. Service providers are therefore critical to clients’ achievement of health and family planning goals. Such services are needed not merely because of individual deficiencies, but also due to the relational nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Although "family values" have sometimes operated as code for white culture (Løvdal Stephens 2019), the harkening to traditional values did not seem to come from a place of political or racist intent for study participants; rather, it was viewed as a way to improve their lives in meaningful ways. However, further research on the racial and political views of the chronically poor is needed.Although culture does matter for the experiences of people in poverty, that does not indicate a coherent or generalizable "culture of poverty"(Seale 2023). Even among those research participants, we observed much variation in adaptations and survival strategies.…”
mentioning
confidence: 57%
“…Although "family values" have sometimes operated as code for white culture (Løvdal Stephens 2019), the harkening to traditional values did not seem to come from a place of political or racist intent for study participants; rather, it was viewed as a way to improve their lives in meaningful ways. However, further research on the racial and political views of the chronically poor is needed.Although culture does matter for the experiences of people in poverty, that does not indicate a coherent or generalizable "culture of poverty"(Seale 2023). Even among those research participants, we observed much variation in adaptations and survival strategies.…”
mentioning
confidence: 57%
“…Next to farms and movements, bodies are a third level where relational autonomy is created. The body is a major site of social control and inequality, especially for girls and women (Seale 2017). Bodily autonomy is relational, as people are "always situated in relation to someone else rather than simply as an individual with a problem" (Seale 2017, p. 332).…”
Section: Relational Autonomymentioning
confidence: 99%